Pengaruh Kepercayaan dan Kemudahan Penggunaan Terhadap Keputusan Pembelian pada Tiktok Shop Oleh Generasi Z - Annisa Putri; Hansen Rusliani; Dessy Anggraini (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The development of e-commerce, especially TikTok Shop, has encouraged changes in the purchasing behavior of Generation Z, particularly those who actively use digital platforms. However, the levels of trust and ease of use that are not yet optimal have become obstacles in purchasing decisions. This study aims to analyze the influence of trust and ease of use on purchasing decisions on TikTok Shop among Generation Z in Jambi. This study employed a quantitative method involving 100 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression. The data analysis techniques included validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination tests with the assistance of IBM SPSS Statistics. The results showed that trust has a positive and significant effect on purchasing decisions partially. In addition, ease of use also has a positive and significant effect on purchasing decisions partially. Simultaneously, trust and ease of use have a positive and significant effect on purchasing decisions. Together, both variables contribute 45.1%, while the remaining 54.9% is influenced by other factors outside this study. In conclusion, trust and ease of use are important factors in increasing purchasing decisions on TikTok Shop, especially among Generation Z.